Diabetic Foot - treatment and prevention - literature review - Edward Wąsiewicz; Aleksandra Kuźniar; Dominik Szawica; Kamila Fularska; Michał Oleszko; Radosław Bernacki; Piotr Bernacki; Martyna Dutka; Witold Zardzewiały; Fryderyk Sobczak (Kazimierz Wielki University, 2023)
Introduction: Diabetic foot is a serious condition affecting large percentage of long term diabetics .Proper diabetic foot treatment, education and prevention can greatly influence quality of life of many diabetics who are at risk of developing this condition. Aim of study: The purpose of the study was to review the latest literature on the most recent diabetic foot treatment, education and prevention. Matherials and methods: A systemic review was conducted using Google Scholar, PubMed and ScienceDirect databases and the search was limited to studies published between 2000 and 2023. The search strategy was based on following terms: diabetic foot, diabetic neuropathy, diabetic ulcer, diabetic foot treatment. Results: We found many different studies which show importance of gut microflora in various different ailments and diseases, we have also found many showing  factors that influence intestinal microbiota composition. Conclusions: diabetic foot is a severe complication of diabetes that requires a multidisciplinary approach to treatment. Prevention is essential, and patients should be educated on the importance of foot care and blood sugar control.With proper treatment and management, diabetic foot can be prevented and effectively treated.